Penerapan Hukum dalam Pemberian Izin Pengelolaan Usaha Pertambangan Batu Bara di Kalimantan - Apip Syaripudin (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2020)
The government as a representation of the state, both central and regional, has an involvement in the management of natural resource products, including mining products, namely in terms of regulation (regulation), exploitation (care) and supervision. The purpose of this study was to determine the arrangements related to licensing in the management of coal businesses in South Kalimantan and post-mining reclamation studies of coal in South Kalimantan. This type of research is a descriptive analysis research with normative juridical approach. The results showed that the system and mechanism regarding the application for mining business licenses were still carried out in accordance with the provisions of Law No. 4 of 2009 concerning Mineral and Coal Mining as well as implementing regulations namely Government Regulation Number 23 of 2010 concerning Implementation of Mineral and Coal Mining Business Activities. And reclamation carried out on ex-mining land in South Kalimantan Province is considered less effectiveKeywords: Application of Law, Mine. Coal AbstrakPemerintah sebagai representasi negara, baik pusat maupun daerah memiliki keterlibatan dalam pengelolaan hasil sumber daya alam, termasuk didalamnya hasil pertambangan yaitu dalam hal pengaturan (regulasi), pengusahaan (mengurus) dan pengawasan. Tujuan penelitian ini adalah untuk mengetahui pengaturan terkait pemberian ijin dalam pengelolaan usaha batu bara di Kalimantan Selatan dan kajian reklamasi pasca tambang batu bara di Kalimantan Selatan. Jenis penelitian ini adalah penelitian deskriptif analisis dengan pendekatan yuridis normatif. Hasil penelitian menunjukan bahwa Sistem dan mekanisme mengenai permohonan izin usaha pertambangan tetap dilaksanakan sesuai ketentuan Undanng-Undang Nomor 4 Tahun 2009 tentang Pertambangan Mineral dan Batubara serta peraturan pelaksananya yaitu Peraturan Pemerintah Nomor 23 Tahun 2010 tentang Pelaksanaan Kegiatan Usaha Pertambangan Mineral dan Batubara serta reklamasi yang dilakukan di lahan bekas tambang di Provinsi Kalimantan Selatan dinilai kurang efektif.Kata kunci: Penerapan Hukum, Tambang. Batu Bara